2021
DOI: 10.1021/acscentsci.1c01109
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and Scalable C(sp3)–H Amination via Decatungstate Photocatalysis Using a Flow Photoreactor Equipped with High-Intensity LEDs

Abstract: Carbon–nitrogen bonds are ubiquitous in biologically active compounds, prompting synthetic chemists to design various methodologies for their preparation. Arguably, the ideal synthetic approach is to be able to directly convert omnipresent C–H bonds in organic molecules, enabling even late-stage functionalization of complex organic scaffolds. While this approach has been thoroughly investigated for C(sp 2 )–H bonds, only few examples have been reported for the direct amination of aliphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…We observed that when the light output was reduced, the conversion dropped significantly, in an almost linear fashion. (30) Subsequently, the reaction was performed at different substrate concentrations. It was found that there was no significant change in conversion when the concentration of the substrate was either increased or decreased.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…We observed that when the light output was reduced, the conversion dropped significantly, in an almost linear fashion. (30) Subsequently, the reaction was performed at different substrate concentrations. It was found that there was no significant change in conversion when the concentration of the substrate was either increased or decreased.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…Ranging from the numbering up of micro- and millireactors to the design of completely novel reactor types, the productivities of photochemical reactors have seen tremendous growth over the past years. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…9,[24][25][26][27][28][29][30][31] The influence of offdiagonal free energies is well precedented in organic hydrogen atom transfer reactions, 32 but their relevance in the broader class of CPET reactions has implications for the mechanism and selectivity of many biological and synthetic systems. [33][34][35][36][37] A central paradox that has recently emerged is how the influence of off-diagonal thermodynamic elements, which is rooted in semiclassical transition state theory, can be reconciled with CPET reactions which are widely acknowledged to be nonclassical or nonadiabatic (Figure 1, right). 16,[38][39][40][41] The specific formulations for how ΔG °PT and ΔG °ET can affect CPET reactivity vary, but are commonly supported by DFT optimized transition states 9,24,27,28 and invoke textbook physical organic concepts such as nonperfect synchronization, imbalanced transition states, and More O'Ferral-Jencks diagrams.…”
Section: Introductionmentioning
confidence: 99%